Ethanol- and heat-mediated phase change from a kinetic (Z′ = 4) polymorph to a thermodynamic (Z′ = 1) polymorph for an N2,6-diaryl-1,3,5-triazine-2,4-diamine - Tan, Sang Loon *; Tan, Yee Seng *; Muhammad Syafiq, Sahari; Junaid, Ahamd; Dolzhenko, Anton V; Tiekink, Edward R. T. * (Royal Society of Chemistry, 2023)
Two polymorphs, α (Z' = 4) and β (Z' = 1), of an N2,6-diaryl-1,3,5-triazine-2,4-diamine derivative have been isolated at different times from ethanol solution. Significant 2 conformational variability in the five independent molecules is apparent. The molecular packing is distinct but features some commonalties such as the formation of eight-membered {···HNCN}2 synthons mediated by phenylamino-N H···N(triazine) hydrogen bonds and (external) supporting amino-N–H···C(phenylamino) contacts. The dimeric aggregates are connected into two-dimensional arrays via triazine-amino-N–H···O(methoxy) hydrogen bonds. In each crystal, the interactions involve chemically equivalent triazine-N, methoxy-O and amino-H atoms. However, the connections between layers is distinct, notably with superimposition of pairs of molecules via π···π stacking between all three aromatic rings in the α-form being restricted to π···π stacking between triazine rings only in the β-form. The experimental molecular structures have been subjected to a conformational analysis and compared to the geometry-optimised molecule. The MEP and NPA have been evaluated, and the molecular packing investigated by the analysis of the calculated Hirshfeld surfaces, interaction energies, NCI plots and energy frameworks. The kinetic α-polymorph crystallises with Z' = 4 and features expansive, stabilising π···π interactions in the molecular packing which is achieved by relatively unstable conformations of three of the four molecules. The αpolymorph is readily converted to the thermodynamic β-polymorph, which has the most stable molecular conformation, in solution, with the egress of time, and in the solid-state via heating of single crystals and powdered samples. The adoption of the crystal form results from an interplay between global molecular packing and stability of molecular conformation.